Pop-Culture Pedagogy in the Music Classroom Teaching Tools from American Idol to YouTube - Biamonte, Nicole; Aarden, Bret; Auerbach, Brent; Bierman, Benjamin; Bostock, Mathonwy; Burns, Lori; Dubuc, Tamar; Grymes, James A.; Hughes, James R.; Kerstetter, Kathleen; Lafrance, Marc; MacLachlan, Heather; et al. (Scarecrow Press, 2010)
This essay collection provides a variety of ideas and techniques for teaching music classes using elements of popular culture, such as popular songs and genres, mixes and remixes, video games, music videos, television shows, and internet resources. Each chapter offers a pedagogical model for incorporating these powerful tools to encourage student interaction in courses on musicianship, music theory, analysis, criticism, music history, and related classes.
Keywords: Music -- Instruction and study; Popular culture -- Study and teaching; Popular music -- Instruction and study; Music : Instruction and study; Popular music : Instruction and study; Popular culture : Study and teaching; Music; Music, Dance, Drama & Film; Music Instruction & Study